2015
DOI: 10.1021/acsmacrolett.5b00150
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Nonlinear Rheological Behavior of Fibrillar Methylcellulose Hydrogels

Abstract: Cryogenic transmission electron microscopy and small-angle neutron scattering recently have revealed that the well-known thermoreversible gelation of methylcellulose (MC) in water is due to the formation of fibrils, with a diameter of 15 ± 2 nm. Here we report that both the linear and nonlinear viscoelastic response of MC solutions and gels can be described by a filament-based mechanical model. In particular, large-amplitude oscillatory shear experiments show that aqueous MC materials transition from shear thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
94
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(106 citation statements)
references
References 35 publications
12
94
0
Order By: Relevance
“…These studies demonstrate that the sol-gel transition is a spinodal process (Takeshita et al 2010) or a nucleation and growth mechanism (Arvidson et al 2012). The cryo-TEM even revealed that MC chains associate into nanofibrils with uniform diameter of 15 ± 2 nm in the MC gels, which clearly explains the formation of optically turbid gel or precipitation (Lott et al 2013a, b;McAllister et al 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These studies demonstrate that the sol-gel transition is a spinodal process (Takeshita et al 2010) or a nucleation and growth mechanism (Arvidson et al 2012). The cryo-TEM even revealed that MC chains associate into nanofibrils with uniform diameter of 15 ± 2 nm in the MC gels, which clearly explains the formation of optically turbid gel or precipitation (Lott et al 2013a, b;McAllister et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Through another methodology, most researchers focus on using instrumental techniques to elucidate the thermodynamic mechanisms involved in the sol-gel transition and/or phase separation. These techniques include turbidity, laser light scattering, viscometry, rheology, differential scanning calorimetry (Arvidson et al 2012;Fairclough et al 2012;Lu et al 2002;Xu et al 2004), and recently by mid/near infrared spectroscopy (Jing and Wu 2013), small-angle neutron scattering combined with cryogenic transmission electron microscopy (cryo-TEM) (Lott et al 2013a, b;McAllister et al 2015). These studies demonstrate that the sol-gel transition is a spinodal process (Takeshita et al 2010) or a nucleation and growth mechanism (Arvidson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] For example, beyond a critical strain value these networks strain-stiffen, which also corresponds to the demonstration of negative normal stress. 11,12,14 Interestingly, such behavior has not been widely reported for semiflexible polysaccharides networks. To address that, here, we investigate the rheological/mechanical properties of a model polysaccharide network, ionically cross-linked alginate hydrogels.…”
mentioning
confidence: 99%
“…It has been pointed out that hydrophobic and hydrophilic regions within cellulose ethers play an important role with respect to thermal behavior, rheology, and solubility . Recent studies by cryogenic transmission electron microscopy and small angle neutron scattering on thermally induced gel formation of MC have shown that prior to gelling, a fibrillar structure is formed which in a yet unknown way form joints, but hydrophobic–hydrophobic interactions of domains probably play an important role. Polysaccharide derivatives are usually prepared by postmodification of their functional groups, the so‐called “polymer analog reaction” and show structural dispersity with respect to molecular weight, regioselectivity, and distribution of substituents over the polymer chains.…”
Section: Introductionmentioning
confidence: 99%